2020
DOI: 10.1177/1076029620943671
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Status and Venous Thromboembolism Risk in African Americans: A Potential Risk Factor in COVID-19

Abstract: Severe acute respiratory syndrome coronavirus 2 infection (COVID-19) is known to induce severe inflammation and activation of the coagulation system, resulting in a prothrombotic state. Although inflammatory conditions and organ-specific diseases have been shown to be strong determinants of morbidity and mortality in patients with COVID-19, it is unclear whether preexisting differences in coagulation impact the severity of COVID-19. African Americans have higher rates of COVID-19 infection and disease-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 94 publications
0
32
0
1
Order By: Relevance
“…63,69 African Americans show a trend toward having higher baseline levels of coagulation factor VIII, von Willebrand factor, thrombin generation, and D-dimer. 63,70 Obesity is an important risk factor of CVD occurrence, which is most popular in the African American population. This phenotype presents a vicious cycle related with the progression of atherothrombosis, due to oxidative stress, chronic thromboinflammatory cascade, and platelet activation.…”
Section: Emerging Issue: Ethnic Differences In Thromboinflammation Symentioning
confidence: 99%
“…63,69 African Americans show a trend toward having higher baseline levels of coagulation factor VIII, von Willebrand factor, thrombin generation, and D-dimer. 63,70 Obesity is an important risk factor of CVD occurrence, which is most popular in the African American population. This phenotype presents a vicious cycle related with the progression of atherothrombosis, due to oxidative stress, chronic thromboinflammatory cascade, and platelet activation.…”
Section: Emerging Issue: Ethnic Differences In Thromboinflammation Symentioning
confidence: 99%
“… 19 A study has reported that male, white, and African American COVID-19 patients may have more significant hypercoagulability. 20 In addition, hypoxia, sepsis, preeclampsia, and postpartum infection are also common risk factors for VTE in COVID-19 patients. 21 22 In other words, all etiologies that lead to hemoconcentration, slow blood rheology, and increased viscosity contribute to the formation of VTE ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“… 4) Meanwhile, African Americans exhibit a trend toward having higher levels of von Willebrand factor, factor VIII, thrombin generation, and D-dimer. 4) 52) Compared to subjects from other ethnic background, East Asians have the lowest levels of fibrinogen, factor VIII and D-dimer. 7) 28) …”
Section: Racial Differences In Thrombogenicity Componentsmentioning
confidence: 99%
“… 98) Individuals of African descent living in the United States or European countries have worse outcomes with COVID-19 than Caucasians and Asians. 52) Their vulnerability is not fully explained by the differences in social and economic factors. 20) Activity of coagulation-inflammation cascade and predisposition to the development of coagulopathy varies between the races, with African Americans trending toward a more prothrombotic state ( Tables 1 and 2 ).…”
Section: Emerging Issues Related With Thrombogenicitymentioning
confidence: 99%